P. Ramlees music: a reflection of culture contact in a multi-ethnic society - Chan Clare Suet Ching, (Universiti Pendidikan Sultan Idris, 2003)
P. Ramlees music: a reflection of culture contact in a multi-ethnic society by Chan Clare Suet Ching,